Addressing resource constraint issues: unpacking the strategies for sustainability of nonprofit organisations / Nur Hayati Ab Samad and Noor Hazlina Ahmad - Ab Samad, Nur Hayati; Ahmad, Noor Hazlina (Accounting Research Institute (ARI), 2022)
Nonprofit organisations (NPOs) play a significant role in social service delivery via deliverables of the organisational mission. However, NPOs operate with limited resources, which consequently trigger their unsustainability. The inability of NPOs to address resource constraint issues may adversely impact society because they play an important role in delivering social services and ensuring sustainable development. Hence, through semi-structured interviews, this study addressed how NPOs operating under limited resources ensure organisational sustainability. The findings indicated that NPOs implement entrepreneurial orientation (EO) and cross-sector collaboration to overcome resource constraints. Concurrently, organisational capacities (human resource capacity, board leadership capacity, infrastructure capacity, and planning and development capacity) are vital to ensure the sustainability of NPOs. Stakeholder engagement is predicted as a moderator between EO and NPOs sustainability. Organisational fit is postulated as a moderator between cross-sector collaboration and NPOs sustainability. The findings contribute to the literature on the sustainability of NPOs by proposing a conceptual framework on organisational factors influencing NPO sustainability. Based on the findings, NPOs and regulators can unpack the targeted strategies that enhance NPO sustainability.